Hypertriglyceridemic waist and arterial hypertension in adults: a systematic review and meta-analysis: Cintura hipertrigliceridémica e hipertensión arterial en adultos: una revisión sistemática y metaanálisis - Reyes Gamonal, Jacqueline M. (2022)
Objective: To develop a systematic review and meta-analysis to determine the association between hypertriglyceridemic waist (CHTG) and arterial hypertension (HBP) in adults. Materials: The present study is a systematic review (SR) with meta-analysis of analytical cross-sectional observational studies. Search strategies will be used in different databases, which will be Pubmed, SCOPUS, Web of Science, Embase. The qualitative analysis was presented in a table with the characteristics of each study. For quantitative analysis, random-effects meta-analysis was performed due to the heterogeneity of the studies. These variables were compared using Odds Ratios (OR) as a measure of association with their corresponding 95% confidence interval. Results: Five studies were included for statistical analysis. Overall, a statistically significant association was found between both variables (OR: 1.36; 95% CI 1.07 to 1.71). In turn, there was a high heterogeneity (I squared 92%). Conclusions: This SR found that CHTG is associated with the presence of hypertension. However, given the few studies found, it is recommended to carry out more primary studies with a prospective design before carrying out a next SR on the subject, and with standardized cut-off points to make a more homogeneous comparability.